Factors affecting Consumer’s Preference of Fast-Food Product in Butwal Sub-Metropolitan City - Pun, Ranjana (Devkota Journal of Interdisciplinary Studies, 2023)
The objective of this study is to examine and assess the determinants that impact the decision-making process of consumers in the Butwal Sub-Metropolitan City with regards to fast food products. The dependent variable in this study is consumer preference, while taste, cost, quality, and service are considered as independent variables. A descriptive and causal research design was employed in this study, with a sample size of 384 participants, primarily comprising students from Butwal Sub-Metropolitan City universities. Primary data is obtained through the utilization of a structured questionnaire. Statistical techniques such as descriptive statistics, Pearson correlation, and regression analysis conducted through the use of SPSS software are commonly employed to ascertain the relationships between the dependent variable, consumer preference, and the independent variables, namely taste, cost, quality, and service. The correlation analysis reveals noteworthy associations among taste, cost, quality, service, and consumer preference. The findings of the regression analysis indicate a statistically significant and positive relationship between consumers preferences for fast food items and factors such as taste, quality, and service. This suggests that consumers prioritize these factors when making decisions regarding fast food options. Conversely, the study suggests that consumer preference is minimally influenced or unaffected by cost, as observed among the participants.